Crystal structure, lattice vibration and microwave dielectric properties of 3CaO·2SiO2·xCaF2 (0 ≤ x ≤ 1.5) ceramics. Issue 10 (15th May 2022) - Qin, Jincheng; Liu, Zhifu; Ma, Mingsheng; Li, Yongxiang
Abstract: The crystal structure, lattice vibration and microwave dielectric properties of 3CaO·2SiO2 · x CaF2 ceramics were investigated in this work. With the increasing of x value, the crystal structure of 3CaO·2SiO2 · x CaF2 ceramics transfers from rankinite (Ca3 Si2 O7 ) to cuspidine (Ca4 Si2 O7 F2 ). The increase of the vibration energy and shrinkage of [SiO4 ] tetrahedral unit hampers the ionic polarization and thus reduces relative permittivity ( ε r ). The enlarged FWHM of the Si–O stretching peak reflects a more drastic anharmonic lattice vibration, resulting in a lower quality factor (Q × f value). The Raman shift of O/F–Ca–O/F bending peak is positively correlated with the temperature coefficient of resonant frequency (τ f ). The microwave dielectric properties of εr and Q × f value (∼@11 GHz) ranging from 7.89 to 8.42, and 21805–46098 GHz, respectively. The stable complex permittivity ( ε r ∗ ) in the frequency range of 20–110 GHz indicates that the fluoride cuspidine ceramics could be a promising candidate for microwave device applications.